Improving the Community Economy Through the Implementation of Digital Marketing and Business Feasibility Studies - Budiarty, Ida; Emalia, Zulfa; Maimunah, Emi; Sitorus, Nurbetty Herlina (Green Publisher Indonesia, 2022)
This community service project aims to assist and encourage Adijaya Village Seedling Garden in developing digital marketing strategies and conducting business feasibility studies. Adijaya Village Seedling Garden (VSG), Pekalongan, East Lampung, is an example of how digital marketing is not commonly employed, especially in areas and villages. Another issue is that partners lack the necessary skills to write Business Feasibility Study Reports. Partners require the creation of a Firm Feasibility Study Report in order to reduce the danger of loss by determining whether or not a business can be run continually. This service activity's execution technique includes training and guidance in order to lay the groundwork for online marketing in Adijaya village and business feasibility studies. This service activity went off without a hitch, and the participants were enthusiastic in their participation. The training participants should be able to understand and implement marketing strategies as well as conduct business feasibility studies as a result of this activity.